Wybory do Bundestagu w 2025 roku - Bielawska, Agnieszka (1977- ); Kruk, Aleksandra (1980- ); Molo, Beata (1976- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The monograph provides a comprehensive political analysis of the elections to the 21st Bundestag, held on 23 February 2025. The authors apply document and party programme analysis alongside historical, comparative, and institutional methods, situating the study within the broader context of changes in Germany`s political system against the backdrop of global and European challenges. The monograph consists of three chapters. The first reconstructs the socioeconomic and political conditions preceding the elections: the crisis of the German economy`s prestige, growing disillusionment with democracy and catch-all parties, the collapse of the SPD-FDP-Greens coalition (2021-2025) under Olaf Scholz, and a highly personalised election campaign dominated by security, migration, and energy policy. It analyses the electoral outcome - the victory of CDU/CSU and the formation of a Grand Coalition with SPD under Friedrich Merz - as well as the rise of the AfD and the marginalisation of the FDP and BSW.
Keywords: wybory do Bundestagu 2025; system partyjny Niemiec; CDU/CSU; SPD; AfD; Merz, Joachim-Friedrich Martin Josef (1955- ); Wielka Koalicja; kampania wyborcza; polityka wewnętrzna; polityka zagraniczna; bezpieczeństwo; NATO; Ukraina; transformacja energetyczna; kryzys gospodarczy; Niemcy; 2025 Bundestag elections; German party system; Grand Coalition; election campaign; domestic policy; foreign policy; security; Ukraine; energy transition; economic crisis; Germany